Negotiating masculinities through the game of distinction - a case study of MOBA gamers at a Chinese university. Issue 3 (1st September 2016) - Chen, Siyu
Abstract : MOBA games – a major site for male bonding – have gained wide popularity in Chinese universities. However, college gamers in general suffer from stigmatization as game addicts and this challenges their senses of masculinity. Based on four months of field study, this article investigates the formation of MOBA gamers' masculinities through diverse game-related practices and discourses, with a particular focus on its intersection with class. Building on Tony Coles' theoretical model of "a field of masculinity, " the article concludes that MOBA games constitute an arena where performances of social class, and recognition of class entitlements, are enacted and coded in a highly gendered way. Arguing that the masculine hierarchy in MOBA gaming culture is not so much about the MOBA games themselves but rather a "game of social distinction, " this article gives insight into how masculine culture in contemporary China is informed by increasing materialism and social stratification.